Muslim Intellectualism in the Wake of the Arab Uprisings (American Journal of Islam and Society, 2011)
With the uprisings in the Middle East and North Africa come scores ofintellectual initiatives and academic investigations geared toward understandingthe forces and motives propelling these unprecedented developments.Conferences are being convened and special issues ofjournals are being dedicated to addressing some aspects of the currentphenomena ‒ not to talk of droves of “experts” (academic tourists?)pouring into the Muslim world for research. In short, the so-called“Arab Spring” ‒ also known by the people from the region as revolution(thawra), uprising (intifāÌa), renaissance (nahÌa) and awakening(ṣaḥwa)1 ‒ has been an intellectual treasure trove for academics in the areasof Middle Eastern Studies, Islamic Studies, and Comparative Politics.But are the attempts to explain these phenomena enough to guide the presentand future Muslim generations to proper trajectories toward sociopoliticaland intellectual success? This editorial is intended to argue that, despitethe potential positive outcomes from recent initiatives, now is the opportunetime for Muslims to seize in order to design future trajectories for their upcominggenerations. The sociopolitical imperatives (civility, freedom, empowerment,pluralism, and happiness, to name a few), to which they aspireto respond, must be guided by, or anchored in, grand intellectual endeavors ...